Looking ahead to the future of GeogEd: Creating spaces of exchange between communities of practice. Issue 1 (9th February 2021) - Finn, Matt; Hammond, Lauren; Healy, Grace; Todd, James D.; Marvell, Alan; McKendrick, John H.; Yorke, Lynda
Abstract: As part of the special issue marking the transition of the Higher Education Research Group to the Geography and Education Research Group, in this final paper we argue that the reformed group has a key role to play in promoting spaces of exchange between the communities of practice that have a stake in the shared endeavours of geography and education. We draw on structured conversations from the group's launch event, existing literature, and our particular vantage points to identify a range of influences – both heritages that we work with and challenges that we face – that shape the interplay of geography and education in our pedagogical contexts. We argue that the GeogEd Research Group can create spaces of productive exchange between three communities of practice: geographies of education research, geography education research, and pedagogic research. As the research group brings these communities of practice together, it facilitates dialogue, creates new avenues for research, and connects and enhances geography teaching practice across education levels. Abstract : We argue that the reformed Geography and Education Research (GeogEd) group of the RGS‐IBG has a key role to play in promoting spaces of exchange between the communities of practice that have a stake in the shared endeavours of geography and education. We draw on structured conversations from the group's launch event, existing literature, and our particular vantage points to identify a range of influences – both heritages that we work with and challenges that we face – that shape the interplay of geography and education in our pedagogical contexts. As the research group brings these communities of practice together, it can facilitate dialogue, create new avenues for research, and connect and enhance geography teaching practice across education levels.